Newspapers coverage of the Egyptian January 25 Revolution: a framing analysis - Ibrahim, Ekram (AUC Knowledge Fountain, 2012)
This study analyzes the different frames used by popular newspapers Al-Ahram and Al-Masry Al-Youm in covering Egypt's January 25 revolution. The researcher conducted a content analysis of news stories and news features of both newspapers during the 18 days of uprisings that started on January 25, 2011 and ended by former President Hosni Mubarak handing over power to the Supreme Council of Armed Forced (SCAF) on February 11, 2011. The study analyzes 241 stories in Al-Ahram and 174 stories in Al-Masry Al-Youm during this period. The researcher imed at exploring the different frames used by each newspaper, whether those frames have varied along the period f study, and how media ownership affected those frames. The results show that during the beginning of the revolution, Al-Ahram newspaper framed the events as "riots" and the protesters as "violent," while Al- Masry Al-Youm framed the events as a "protest" and the protesters as "the people." The coverage of both newspapers varied along the 18 days of uprisings. Al-Ahram took the revolutionaries' side during the last couple of days, while Al-Masry Al-Youm started delegitimizing the protesters during the same period. The type of media ownership played a significant role in the framing of Egypt's January 25 revolution.